Photodynamic Vaccination of BALB/c Mice for Prophylaxis of Cutaneous Leishmaniasis Caused by Leishmania amazonensis - Viana, Sayonara M.; Celes, Fabiana S.; Ramirez, Laura; Kolli, Bala; Ng, Dennis K. P.; Chang, Kwang P.; de Oliveira, Camila I. (Frontiers in Microbiology, 2018)
Background: Photosensitizers (PS), like porphyrins and phthalocyanines (PC) are excitable by light to generate cytotoxic singlet oxygen and other reactive oxygen species in the presence of atmospheric O2. Photodynamic inactivation of Leishmania by this means renders them non-viable, but preserves their effective use as vaccines. Leishmania can be photo-inactivated after PS-sensitization by loading via their endocytic uptake of PC or endogenous induction of transgenic mutants with delta-aminolevulinate (ALA) to accumulate cytosolic uroporphyrin I (URO). Here, PS-sensitization and photo-inactivation of L. amazonensis was further examined in vitro and in vivo for vaccination against cutaneous leishmaniasis. Methods and Results: L. amazonensis promastigotes were photodynamically inactivated in vitro by PC-loading followed by exposure to red light (1-2 J/cm2) or ALA-induction of uroporphyrinogenic transfectants to accumulate cytosolic URO followed by longwave UV exposure. When applied individually, both strategies of photodynamic inactivation were found to significantly, albeit incompletely abolish the MTT reduction activities of the promastigotes, their uptake by mouse bone marrow-derived macrophages in vitro and their infectivity to mouse ear dermis in vivo. Inactivation of Leishmania to completion by using a combination of both strategies was thus used for the sake of safety as whole-cell vaccines for immunization of BALB/c mice. Different cutaneous sites were assessed for the efficacy of such photodynamic vaccination in vivo. Each site was inoculated first with in vitro doubly PS-sensitized promastigotes and then spot-illuminated with white light (50 J/cm2) for their photo-inactivation in situ. Only in ear dermis parasites were photo-inactivated beyond detection. Mice were thus immunized once in the ear and challenged 3 weeks later at the tail base with virulent L. amazonensis. Prophylaxis was noted in mice photodynamically vaccinated with doubly photo-inactivated parasites, as indicated by a significant delay in the onset of lesion development and a substantial decrease in the parasite loads. Conclusion: Leishmania doubly PS-sensitized and in situ photo-inactivated as described proved to be safe and effective when used for one-time immunization of ear dermis, as indicated by its significant protection of the inherently very susceptible BALB/c mice against cutaneous leishmaniasis.